1980
DOI: 10.1172/jci109815
|View full text |Cite
|
Sign up to set email alerts
|

In vivo oxygen transport in the normal rabbit femoral arterial wall.

Abstract: A B S T R A C T In vivo measuremnents of tissue oxygen tension were malde at 10-,um intervals through functioning itn situ ral)b)it femoral arterial walls, using inhalation anesthesia anid recessed microcathodes with -4-gium external diameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…In each case a curve has been defined, with maximum wall oxygenation immediately adjacent to the vessel lumen, which diminished progressively to a trough level in the middle to outer media and rose progressively again toward the adventitia. This profile was consistent in its overall shape and is similar to profiles obtained in the dog by Heistad and Marcus 10 and in the rabbit by Crawford et al 15 and Crawford and Kramsch.…”
Section: Discussionsupporting
confidence: 89%
“…In each case a curve has been defined, with maximum wall oxygenation immediately adjacent to the vessel lumen, which diminished progressively to a trough level in the middle to outer media and rose progressively again toward the adventitia. This profile was consistent in its overall shape and is similar to profiles obtained in the dog by Heistad and Marcus 10 and in the rabbit by Crawford et al 15 and Crawford and Kramsch.…”
Section: Discussionsupporting
confidence: 89%
“…Neointimal thickening 1 mo after angioplasty was found to contribute to only a minor portion ofthe loss in diameter after either BA or LBA, and medial thickness was found to be similar to that reported by others for the normal rabbit femoral artery (41). Several groups of investigators have suggested that visco-elastic recoil frequently contributes to luminal compromise after conventional balloon angioplasty (42,43).…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that HIF-1␣ and VEGF expression was evident in the outer to middle layers of medial SMCs (Figure 3), which are known to be vulnerable to hypoxia. 9,10 It has been shown that HIF-1␣ protein levels increase markedly as cellular oxygen concentration is reduced and decay rapidly when cells are returned to a nonhypoxic environment. 16 The role of HIF-1␣ in activation of VEGF gene transcription is established in hypoxic cells.…”
Section: Hif-1␣ Induction In Hypertensive Aortamentioning
confidence: 99%
“…8 However, medial thickening may create the hypoxic zone in the media by increasing the distance required for oxygen diffusion from the lumen. 9,10 Because hypertension produces medial thickening, it is conceivable that the AVV plays a role in the maintenance of homeostasis during vascular remodeling in hypertensive arteries. However, there has been little study of the AVV in hypertensive arteries.…”
mentioning
confidence: 99%